2014
DOI: 10.1016/j.jvs.2013.07.117
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic endovascular aortic repair in management of aortoesophageal fistulas

Abstract: Late infection or recurrence of the AEF and associated mortality rates are high when TEVAR is used as a sole therapeutic strategy. Prolonged antibiotic treatment has a strong negative association with mortality. A strategy of a temporizing endovascular procedure to stabilize the patient in extremis, and upon recovery, an open surgical esophageal repair with or without stent graft explantation is advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 54 publications
1
107
3
2
Order By: Relevance
“…Most commonly parenteral antibiotics are given for 2 to 8 weeks post-procedure, but whether lifelong oral antibiotics are necessary is debatable [6]. Most recently, Canaud et al reviewed the outcomes of TEVAR for AEF and reported that prolonged antibiotic treatment (i.e., greater than 4 weeks) was associated with significantly lower aortic mortality [7].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly parenteral antibiotics are given for 2 to 8 weeks post-procedure, but whether lifelong oral antibiotics are necessary is debatable [6]. Most recently, Canaud et al reviewed the outcomes of TEVAR for AEF and reported that prolonged antibiotic treatment (i.e., greater than 4 weeks) was associated with significantly lower aortic mortality [7].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the incidence of infection around the graft expanding to the esophagus was reported to be 0.5-5%, and has been proposed as having a central role in the development of post-TEVAR AEF [22]. In a review article, micro-organisms were reported in 43.2% of the patients after TEVAR for AEF, and, in 31.2% of the patients with inflammation, highly virulent pathogens, such as methicillin-resistant Staphylococcus aureus, Streptococcus spp., Gram-negative species, such as Pseudomonas and Klebsiella, or Coxiella burnetti were isolated [28,41]. These findings suggest that micro-organisms associated with the post-TEVAR AEF formation could hardly be controlled with general use of antibiotic therapy [32].…”
Section: Mechanism Of Post-tevar Aefmentioning
confidence: 97%
“…Several complications of TEVAR, including paraplegia, stroke, post-implantation embolisms and AEF, have been reported [21][22][23][24][25][26][27][28][29][30]. The incidence of post-TEVAR AEF was reported to be 1.7-1.9%, comparable to the incidence after open surgery for TAA, resulting in a high rate of re-stenting for AEF recurrence [21][22][23].…”
Section: Etiologies Of Aorto-esophageal Fistulamentioning
confidence: 99%
See 2 more Smart Citations